2008
DOI: 10.1530/eje-07-0558
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone pulse therapy for patients with moderately severe Graves' orbitopathy: a prospective, randomized, placebo-controlled study

Abstract: Objective: To assess whether methylprednisolone (MP) pulse therapy is efficacious in the treatment of moderately severe Graves' orbitopathy (GO). Design: Prospective, placebo (PL)-controlled, double-blind, randomized study. Methods: Fifteen previously untreated patients with active, moderately severe GO participated in the study; 6 patients received MP and 9 patients a PL. Moderately severe disease was defined using the NOSPECS classification of clinical signs of GO . Activity was measured with the clinical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 26 publications
(31 reference statements)
5
61
0
5
Order By: Relevance
“…Monthly regimen is not a commonly used strategy in the treatment of GO [5] and characterized by a larger dose at each cycle (1.5 g iv MP) and a long interval (4 weeks) between any two cycles [18]. Clinical trials [6,7] have showed that with the same administration method, a better response was proportional to receiving larger doses of iv MP in the range of safe dosage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Monthly regimen is not a commonly used strategy in the treatment of GO [5] and characterized by a larger dose at each cycle (1.5 g iv MP) and a long interval (4 weeks) between any two cycles [18]. Clinical trials [6,7] have showed that with the same administration method, a better response was proportional to receiving larger doses of iv MP in the range of safe dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Eligible patients meeting the inclusion criteria were randomly assigned to the monthly regimen (MR) [18] group or weekly regimen (WR) [1,5] group according to a random number table. The MR was as follows: 0.5 g iv MP daily for three consecutive days (pulse therapy on days 1, 2, and 3 in weeks 1, 5, 9, and 13) over 4 cycles at 4 weekly intervals, for a total dose of 6.0 g over 3 months.…”
Section: Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficacy and safety of different IV glucocorticosteroid therapy protocols are still under debate. Presently, there are no generally accepted recommendations or guidelines for treatment of GO [20,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%